PERBANDINGAN KINERJA KEUANGAN PT. BRI DAN PT. BRI SYARIAH TAHUN 2011-2014 - Prasetya, Ferry Anggara; C, Niken Wahyu (PERMANA, 2016)
Comparison of Financial Performance of PT. BRI and PT. BRI Syariah Year 20112014. The purpose of this study was to determine the difference between the financial performance of PT. BRI with the financial performance of PT. BRI Syariah Year 20112014. Data collection methods used in this study are library study methods and documentation methods. While the data analysis method used is a two different test method on average. Based on the equation there is a significant difference in the financial performance of PT. BRI with the financial performance of PT. BRI Syariah Year 2011-2014 at the capital adequacy ratio is known from the calculation results of SPSS obtained a significance value of 0.043 <0.05. There is a significant difference in the financial performance of PT. BRI with the financial performance of PT. BRI Syariah Year 2011-2014 on return on equity is known from the results. SPSS calculation obtained a significance value of 0,000 <0,05. There is a significant difference in performance finance of PT. BRI with the financial performance of PT. Sharia BRI Year 2011-2014 on Operating Expenses against Operating Income (BOPO) is known from the calculation results of SPSS obtained a significance value of 0,000 < 0.05. There is a significant difference in the financial performance of PT. BRI with the financial performance of PT. BRI Syariah Year 2011-2014 on the Loan to Deposit Ratio (LDR) is known from the results of SPSS calculations obtained a significance value of 0,000 <0,05. There is a difference in the financial performance of conventional banking with the financial performance of Islamic banking on non-performing loans (NPL) known from the results of SPSS calculations obtained a significance value of 0.004 <0.05. Keywords : CAR, ROE, BOPO, LDR, NPL. A